Phytobiomes are compositionally nested from the ground up - Anthony S. Amend; Gerald M. Cobian; Aki J. Laruson; Kristina Remple; Sarah J. Tucker; Kirsten E. Poff; Carmen Antaky; Andre Boraks; Casey A. Jones; Donna Kuehu; Becca R. Lensing; Mersedeh Pejhanmehr; et al. (PeerJ, 2019)
Plant-associated microbes are critical players in host health, fitness and productivity. Despite microbes’ importance in plants, seeds are mostly sterile, and most plant microbes are recruited from an environmental pool. Surprisingly little is known about the processes that govern how environmental microbes assemble on plants in nature. In this study we examine how bacteria are distributed across plant parts, and how these distributions interact with spatial gradients. We sequenced amplicons of bacteria from the surfaces of six plant parts and adjacent soil of Scaevola taccada, a common beach shrub, along a 60 km transect spanning O’ahu island’s windward coast, as well as within a single intensively-sampled site. Bacteria are more strongly partitioned by plant part as compared with location. Within S. taccada plants, microbial communities are highly nested: soil and rhizosphere communities contain much of the diversity found elsewhere, whereas reproductive parts fall at the bottom of the nestedness hierarchy. Nestedness patterns suggest either that microbes follow a source/sink gradient from the ground up, or else that assembly processes correlate with other traits, such as tissue persistence, that are vertically stratified. Our work shines light on the origins and determinants of plant-associated microbes across plant and landscape scales.